The Archaeology of Iran from the Palaeolithic to the Achaemenid Empire - Matthews, Roger (Routledge World Archaeology, 2022)
The Archaeology of Iran from the Palaeolithic to the Archaemenid Empire is the first modern academic study to provide a synthetic, diachronic analysis of the archaeology and early history of all of Iran from the Palaeolithic period to the end of the Achaemenid Empire at 330 BC. Drawing on the authors' deep experience and engagement in the world of Iranian archaeology, and in particular on Iran-based academic networks and collaborations, this book situates the archaeological evidence from Iran within a framework of issues and debates of relevance today. Such topics include human-environment interactions, climate change and societal fragility, the challenges of urban living, individual and social identity, gender roles and status, the development of technology and craft specialisation and the significance of early bureaucratic practices such as counting, writing and sealing within the context of evolving societal formations. Richly adorned with more than 500 illustrations, many of them in colour, and accompanied by a bibliography with more than 3000 entries, this book will be appreciated as a major research resource for anyone concerned to learn more about the role of ancient Iran in shaping the modern world.